2017
DOI: 10.1093/jac/dkx441
|View full text |Cite
|
Sign up to set email alerts
|

Fosfomycin efficacy and emergence of resistance among Enterobacteriaceae in an in vitro dynamic bladder infection model

Abstract: Using dynamic in vitro simulations of urinary fosfomycin exposures, E. coli and E. cloacae isolates with MIC >16 mg/L, and all K. pneumoniae isolates, were not reliably killed. Emergence of resistance was significant. This challenges fosfomycin dosing and clinical breakpoints, and questions the utility of fosfomycin against K. pneumoniae. Further work on in vitro dose optimization is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 39 publications
2
19
1
Order By: Relevance
“…In addition, emergence of resistance was often detected early, within the first 24 h, such that repeat doses of fosfomycin given after that time had very little impact on the overall bacterial density. This rapid emergence of resistance negated the benefit of giving multiple doses and particularly questions the role of delaying repeat doses by 48 or 72 h. Overall, the efficacy of fosfomycin against our K. pneumoniae isolates appeared limited, regardless of the baseline MIC or drug exposure, a finding supported by other studies (40)(41)(42).…”
Section: Figsupporting
confidence: 68%
See 1 more Smart Citation
“…In addition, emergence of resistance was often detected early, within the first 24 h, such that repeat doses of fosfomycin given after that time had very little impact on the overall bacterial density. This rapid emergence of resistance negated the benefit of giving multiple doses and particularly questions the role of delaying repeat doses by 48 or 72 h. Overall, the efficacy of fosfomycin against our K. pneumoniae isolates appeared limited, regardless of the baseline MIC or drug exposure, a finding supported by other studies (40)(41)(42).…”
Section: Figsupporting
confidence: 68%
“…Fosfomycin exposure in the bladder infection in vitro model. We used an adaptation of a previously described in vitro model (40). Observed in vitro concentrations closely matched the target concentration of each of the single and multidose fosfomycin exposure simulations.…”
Section: Resultsmentioning
confidence: 99%
“…28 Urinary concentrations following a single 3 g dose are generally sufficient to treat patients infected with susceptible organisms, although some recent data suggest more variability in urinary concentrations than previously thought. 33,34 As fosfomycin has a unique structure there is minimal cross-resistance with other antibiotics. At present, many multidrug resistant isolates remain susceptible to fosfomycin, even in geographic regions where there has been widespread use of the drug.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…A fosfomycin exposure of an AUC0-24/MIC ≥ 3136 has been shown to suppress the emergence of resistance for E. coli and E. cloacae isolates with an MIC ≤8 mg/L. With a breakpoint of 8 mg/L, it may be possible to treat and prevent the emergence of resistance for systemic infections in most patients who receive a dose of 8 g administered thrice-daily (268), or to treat a urinary tract infection with a single 3 g oral dose (214). However, fosfomycin resistance may emerge during treatment for K. pneumoniae or non-fermenting Gram negative bacterial infections.…”
Section: Discussionmentioning
confidence: 99%
“…reported that continuous infusion of ceftazidime exhibited improved bacterial killing compared to an intermittent infusion against P. aeruginosa (30). In a separate study, an extended PTZ infusion, but not an intermittent infusion, suppressed the emergence of resistance of P. aeruginosa (214).…”
Section: Introductionmentioning
confidence: 95%